Three new phenolic acid derivatives from Oenothera biennis. (December 2022) - Liu, Juan-Juan; Zhang, Jing-Ke; Zhang, Qin-qin; Zhu, Deng-Hui; Wei, Jun-Jun; Li, Meng; Zheng, Xiao-ke; Feng, Wei-Sheng
Abstract: Three new phenolic acid derivatives, 1-methyl glyceric acid-2-vanillic acid ether (1 ), methyl 2-hydroxy-6-(3-methoxy-3-oxoprop-1-en-2-yloxy) benzoate (2 ), methyl 2-hydroxy-6-(1-Carboxyvinyloxy) benzoate (3 ) and five known compounds namely 4-hydroxymellein (4 ), mellein methyl ether (5 ), 2-methyl-5, 7-dihydroxychromone (6 ), latifolicinin C (7 ) and oresbiusin A (8 ) were isolated from Oenothera biennis L. The structures of these secondary metabolites were elucidated using different spectroscopic techniques, including 1 H, 13 C NMR, HR-ESI-MS, ECD and comparison with published data. Graphical Abstract: ga1 Highlights: Eight compounds including three new natural products were isolated from the whole herbs of Oenothera biennis L. (Onagraceae). The new metabolites were methoxylated phenolic acid derivatives possessing ether functionalities. Their structures were elucidated on the basis of NMR, HRESIMS and ECD spectroscopic data.